Facile and Efficient Fabrication of Bandgap Tunable Carbon Quantum Dots Derived From Anthracite and Their Photoluminescence Properties - Jia, Jianbo; Sun, Yue; Zhang, Yaojie; Liu, Quanrun; Cao, Jianliang; Huang, Guangxu; Xing, Baolin; Zhang, Chuanxiang; Zhang, Lina; Cao, Yijun (Frontiers in Chemistry, 2020)
Low-cost and earth-abundant coal has been considered to have a unique structural superiority as carbon sources of carbon quantum dots (CQDs). However, it is still difficult to obtain CQDs from raw coal due to its compactibility and lower reactivity, and the majority of the current coal-based CQDs usually emit green or blue fluorescence. Herein, a facile two-step oxidation approach (K2FeO4 pre-oxidation and H2O2 oxidation) was proposed to fabricate bandgap tunable CQDs from anthracite. The K2FeO4 pre-oxidation can not only weaken the nonbonding forces among coal molecules which cause the expansion of coal particles, but also form a large number of active sites on the surface of coal particles. The above effects make the bandgap tunable CQDs (blue, green or yellow fluorescence) can be quickly obtained from anthracite within 1 h in the following H2O2 oxidation by simply adjusting the concentration of H2O2. All the as-prepared CQDs contain more than 30 at% oxygen, and the average diameters of which are less than 10 nm. The results also indicate that the high oxygen content only can create new energy states inside the band gap of CQDs with average diameter more than3.2±0.9 nm, which make the as-prepared CQDs emit green or yellow fluorescence.